Review of MXenes as a component in smart textiles and an adsorbent for textile wastewater remediation - Farhana, Kaniz; Kadirgama, Kumaran; Faisal Mahamude, Abu Shadate; Jose, Rajan (Elsevier B.V., 2024)
Two-dimensional (2D) MXenes have emerged as an archetypical layered material combining the properties of an organic-inorganic hybrid offering materials sustainability for a range of applications. Their surface functional groups and the associated chemical properties' tailorability through functionalizing MXenes with other materials as well as hydrophilicity and high conductivity enable them to be the best successor for various applications in textile industries, especially in the advancement of smart textiles and remediation of textile wastewater. MXene-based textile composite performs superb smartness in high-performance wearables as well as in the reduction of textile dyes from wastewater. This article critically reviews the significance of MXenes in two sectors of the textile industry. Firstly, we review the improvement of textile raw materials such as fiber, yarn, and fabric by using MXene as electrodes in supercapacitors, pressure sensors. Secondly, we review advancements in the removal of dyes from textile wastewater utilizing MXene as an absorbent by the adsorption process. MXene-based textiles demonstrated superior strength through the strong bonding between MXene and textile structures as well as the treatment of adsorbate by adsorbent (MXene in the adsorption process). We identify critical gaps for further research to enable their real-life applications.